2023
DOI: 10.3390/agriculture13071278
|View full text |Cite
|
Sign up to set email alerts
|

Improved Apple Fruit Target Recognition Method Based on YOLOv7 Model

Abstract: This study proposes an improved algorithm based on the You Only Look Once v7 (YOLOv7) to address the low accuracy of apple fruit target recognition caused by high fruit density, occlusion, and overlapping issues. Firstly, we proposed a preprocessing algorithm for the split image with overlapping to improve the robotic intelligent picking recognition accuracy. Then, we divided the training, validation, and test sets. Secondly, the MobileOne module was introduced into the backbone network of YOLOv7 to achieve pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 43 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…In order to further verify the performance of the improved YOLOv8 model, this 2 study set up an ablation test to verify the performance of four groups of networks. YOLOv8+FocalModulation [26],YOLOv8 [27],YOLOV8+dysnakeconv [28] the algorithm in 2 3 this paper analyze the performance of four groups of networks from a quantitative perspective. The 1000 cherry images in the test set are objectively evaluated, and the evaluation indicators include model detection accuracy, average detection time, etc.…”
Section: Ablation Test Of Improved Yolo V8 Modelmentioning
confidence: 99%
“…In order to further verify the performance of the improved YOLOv8 model, this 2 study set up an ablation test to verify the performance of four groups of networks. YOLOv8+FocalModulation [26],YOLOv8 [27],YOLOV8+dysnakeconv [28] the algorithm in 2 3 this paper analyze the performance of four groups of networks from a quantitative perspective. The 1000 cherry images in the test set are objectively evaluated, and the evaluation indicators include model detection accuracy, average detection time, etc.…”
Section: Ablation Test Of Improved Yolo V8 Modelmentioning
confidence: 99%
“…The results indicated that the AP value of corn reached 96.3%, and the AP value of weeds reached 88.9%. Yang et al (2023a) improved the YOLOv7 algorithm to identify fruits. The improved YOLOv7 algorithm achieved an accuracy rate of 96.7% on the test set.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the robust detection precision offered by current fruit detection methods utilizing deep learning technologies, they still encounter several challenges, including complex network structures, a multitude of parameters, and slower system operation [33][34][35]. Therefore, this study seeks to design a real-time pineapple detection model for agricultural harvesting robots, proposing a lightweight deep learning model known as MSGV-YOLOv7.…”
Section: Introductionmentioning
confidence: 99%